1996
DOI: 10.1177/017084069601700401
|View full text |Cite
|
Sign up to set email alerts
|

Change as an Underlying Theme in Professional Service Organizations: An Introduction

Abstract: This special issue is dedicated to the theme of change within and around the Professional and Human Service Organizations. The introduction points out the ongoing changes in the societal, economic and business environments within which the professions and professional firms are embedded. We suggest that the reality of such environmental changes brings to the fore questions that are important for the research agenda on the professions. Several such issues are raised, like the impact of advanced information tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 21 publications
1
49
0
2
Order By: Relevance
“…and, following the conceptualisation offered by a range of writers (von Nordenflycht, 2010, Greenwood et al, 2007, Sharma, 1997, one in which services are delivered by professionals (Lowendahl, 2000:18). They embody the fundamental characteristics of the PSF: a professionalized workforce and a dependence upon a substantial body of complex information (von Nordenflycht, 2010); low capital intensity, particularly in terms of specialised plant (Teece, 2003, von Nordenflycht, 2010; a work force comprising of 'sophisticated users of information' who possess quantitatively and qualitatively greater knowledge of their chosen areas (Benner, 2010); specialised expertise gained through training or experience (Starbuck, 1992, Greenwood andLachman, 1996), high recruitment and retentions costs (Teece, 2003) and; a lack of knowledge depreciation (Boone et al, 2008). It has been argued that forces of globalisation mean that PSFs are obliged to follow international clients into markets (Greenwood and Lachman, 1996).…”
Section: Micro-level Context For the Study: Securities Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…and, following the conceptualisation offered by a range of writers (von Nordenflycht, 2010, Greenwood et al, 2007, Sharma, 1997, one in which services are delivered by professionals (Lowendahl, 2000:18). They embody the fundamental characteristics of the PSF: a professionalized workforce and a dependence upon a substantial body of complex information (von Nordenflycht, 2010); low capital intensity, particularly in terms of specialised plant (Teece, 2003, von Nordenflycht, 2010; a work force comprising of 'sophisticated users of information' who possess quantitatively and qualitatively greater knowledge of their chosen areas (Benner, 2010); specialised expertise gained through training or experience (Starbuck, 1992, Greenwood andLachman, 1996), high recruitment and retentions costs (Teece, 2003) and; a lack of knowledge depreciation (Boone et al, 2008). It has been argued that forces of globalisation mean that PSFs are obliged to follow international clients into markets (Greenwood and Lachman, 1996).…”
Section: Micro-level Context For the Study: Securities Firmsmentioning
confidence: 99%
“…They embody the fundamental characteristics of the PSF: a professionalized workforce and a dependence upon a substantial body of complex information (von Nordenflycht, 2010); low capital intensity, particularly in terms of specialised plant (Teece, 2003, von Nordenflycht, 2010; a work force comprising of 'sophisticated users of information' who possess quantitatively and qualitatively greater knowledge of their chosen areas (Benner, 2010); specialised expertise gained through training or experience (Starbuck, 1992, Greenwood andLachman, 1996), high recruitment and retentions costs (Teece, 2003) and; a lack of knowledge depreciation (Boone et al, 2008). It has been argued that forces of globalisation mean that PSFs are obliged to follow international clients into markets (Greenwood and Lachman, 1996). We argue that this also segues with Johanson and Vahlne's (2009) network perspective on internationalisation and that this is an appropriate perspective to adopt for the highly globalised financial services sector, of which securities firms form a part.…”
Section: Micro-level Context For the Study: Securities Firmsmentioning
confidence: 99%
“…It became possible in a situation where the Board feared that the Ministry would put the hospital into trusteeship.' (Denis et al 1996: 681) Indeed, there has been increasing interest in analysing how (former) public-sector organizations have interpreted, coped with, and responded to the major challenges, in particular financial tightening and ideological managerialism over the past two decades (for example, Greenwood and Lachman 1996). Kitchener et al (2000: 224), for example, identified substantial 'resilience of traditional patterns' of work structures and processes in local authority social service departments.…”
Section: Engagement With the Literaturementioning
confidence: 99%
“…This is an integral part of the General Agreement on Trade in Services (defined as GATS Mode 4) (Organization for Economic Cooperation and Development [OECD], 2003). In professional services, which encompass knowledge-intensive, often tailor-made and highly idiosyncratic services built on reputation and established credentials, the liberalization of trade in "natural persons" (GATS Mode 4) is essential for the firm to circulate knowledge and expertise across borders, embodied in the tacit professionalism and expertise of the archetypal "professions" like architects, accountants, or lawyers (Greenwood & Lachman, 1996;Morris & Empson, 1998;Lowendal, Revang, & Fosstenlokken, 2001). The key asset of a service firm (PSF) is the knowledge capacity of its labor force of both managers and professionals, with capital accumulated, clients courted and serviced, and revenues and profits ultimately accrued through the performance of this workforce and its successful interaction with the client.…”
Section: Global Staffing and Expatriation In Professional Service Firmsmentioning
confidence: 99%